Is There a Narrator in This Narrative? - BOUSSAFSAF, Myriam (Journal of Human Sciences, 2014)
Some narratologists insist on the fact that a narrative cannot do without a narrator that has to be distinguished from the real author. Indeed, the narrator is considered as that mediating agency whose task is to prepare the reader’s entrance to the diegetic world by organizing all the necessary elements which may facilitate this entrance. This is what has been labelled the pan-narrator theory.Others, on the other hand, advocate the idea that not all fictional narratives contain a fictional narrator (Köppe/Stühring 2011). Hence, they adopt something called the no-narrator theory.These positions lead us to raise such questions as: do all narratives contain a narrator? And if not, does the death of the narrator engender the death of the narrative?